Pengaruh Investasi Terhadap Pertumbuhan dan Pembangunan Ekonomi - Ain’, Novita Nurul (INAIFAS Press, 2021)
This study is to describe economic growth in today have an impact on the lives of residents in a country. And all of them will affect the welfare of the people. So with the investment, the growth in a country will increase because of a lot investors who will invest in the country. The capital from these investors will be intended for production process, so that it will produce goods and services which of course will be used by the whole community Indonesia. Even so, investment is not a benchmark which is used as collateral for the Indonesian economy however investment is just one of the factors of growth and economic development in Indonesia to be more advanced and more well